Causes of End Stage Kidney Disease in Maintenance Hemodialysis Patients in District Swat, Khyber Pukhtonkhwa Pakistan - Khalid, Fawad; Khan, Asad ullah; Fazal, Adnan (Pakistan Journal of Kidney Diseases, 2021)
Chronic kidney disease (CKD) affects 10–15% of the population worldwide and its prevalence is increasing. Objective: To find the frequency of common diseases causing chronic kidney diseases (CKD) in dialysis dependent patients in District Swat, Khyber Pukhtonkhwa. Methodology: Cross sectional study at Department of Nephrology Nawaz Sharif Kidney Hospital, District Swat, Khyber Pukhtonkhwa, Pakistan. Results: Total of 110 patients were undergoing maintenance hemodialysis. There were 53(48.2%) male and mean age was 54.40+ 16.32 years. Among 110 patients, only 9 (8.2%) had dialysis once per week and 101(91.8%) had dialysis twice per week hemodialysis. Majority, 64(58.2%) patients were undergoing dialysis less than one year. 6(5.5 %) had hypertension, 33(30%) had diabetes and 68(61.8%) patients had both Diabetes and Hypertension. Out of 110, 39(35.5%) patients were Hepatitis B positive, and 28(25.5%) patients had Hepatitis C. Conclusion: Results of this study showed that the leading cause of chronic kidney disease (CKD) among dialysis patients was diabetes mellitus with or without hypertension and a high prevalence of both HBV and HCV.